(untitled) (Revista de Ciências Agroveterinárias, 2023)
Corn is a promising commodity economically for cultivation. Apart from not requiring a long harvest time, sweet corn has a high selling value, without a long post-harvest process. The location of research was conducted in rice fields in Tawangargo Village, Karangploso District, Malang Regency. Altitude ± 749 m above sea level. The implementation was carried out from December 2019 to July 2020. The research design was carried out using a Complete Randomized Block Design, with 2 factors. Factor 1, is the recommended fertilizer dosage of 3 doses (0, ½, and 1 dose), and the second factor is the dose of liquids fertilizer organic (0, 4, 8, and 12 g / l) with 4 repetitions, with intervals of 7-10 once a day. Giving 4 ml / l dose of inorganic fertilizer at an interval of once a week, together with 1 recommended dosage of Makro fertilizer affects the growth and yield of sweet corn plants. The highest production per ha in this treatment was 13,339 kg. The highest RAE value is 325.6% in the recommended 1 dose of NPK treatment plus 4 g / l of "liquids fertilizer organic". The economic approach is by calculating the R/C ratio, the treatment with the highest RAE is the R/C ratio of 8.59 with a net income of Rp. 176,785,041, -